DETECTION OF SELLING DEAD CHICKEN MEAT (TIREN) IN FOUR TRADITIONAL MARKETS OF DENPASAR - Swari, Luh Putu Pradnya; Agustina, Kadek Karang; Swacita, Ida Bagus Ngurah; Suada, I Ketut (Buletin Veteriner Udayana; Vol. 11 No. 2 Agustus 2019DO - 10.24843/bulvet.2019.v11.i02.p06, 2019)
Tiren chickens are basically carcasses, namely chickens that die not because of slaughter, but chickens that have previously died due to poor endurance during the trip or affected by the disease then deliberately slaughtered for sale on the market. This study aims to detect the possibility of yesterday's sale of dead chicken meat (tiren) sold in four traditional markets in Denpasar City. The method used in this study is the purposive sampling method, which was a total of 72 samples of chicken meat were taken from four traditional markets in Denpasar City, each with three samples per market with six replications. The variables tested in this study were detection of tiren chicken with Malachite green test and pH test for chicken meat. The results showed that 19.44% (14/72) samples showed positive Malachite green test and average chicken meat pH 5.93 (5.32 - 6.45). Based on the results of the study it can be concluded that 19.44% chicken meat sold in four traditional markets in Denpasar City, it is suspected that tiren chicken is suggested to consumers to be more selective in choosing chicken meat for consumption